COMPREENSÃO DOS CONCEITOS DE DERIVADA CLÁSSICA E DERIVADA FRACA: ANÁLISE SEGUNDO O MODELO COGNITIVO APOS - Rachelli, Janice (2017)
The present study is on the field of Mathematics Education in higher education and is focused on the teaching and learning of Calculus concepts, specifically related to the concepts of classical derivative and weak derivative. The work, developed in the context of a qualitative research, aims to investigate how some students of the Master degree course in Teaching Mathematics of a community institution in Rio Grande do Sul comprehend the concepts of classical derivative and weak derivative. The APOS theory serves as a theoretical and methodological reference for the elaboration of the genetic decomposition in which the possible mental constructions used by the students were described in what the understanding of the concepts of classical derivative and weak derivative concern. We proposed some activities on the historical constructions of the classical concept, the derivative in the present times, and the passage from the classical derivative to the weak derivative. The teaching situations were developed in the classroom in the second semester of 2016, within the subject of Fundamentals of Differential and Integral Calculus. The basis for these activities was the ACE teaching cycle. The results obtained by analyzing the students' records in the proposed activities and the observations recorded in the field diary indicate that the students were able to coordinate actions and processes in order to obtain the derivative and verify if a function is differentiable. They could also coordinate the interpretations of the derivative, such as slope of the tangent line, instantaneous velocity and rate of variation, besides using mechanisms of generalization and reversibility in the analysis of the graphs of functions and their derivatives and encapsulating the processes necessary for a satisfactory understanding of the concept of the classical derivative. By means of the integral equation, the integration formula by parts, and the fundamental theorem of Calculus, the students were able to coordinate the function and intervals, the functions with compact support by means of internalizing actions and processes for the encapsulation of the mathematical object and weak derivative. Although there are some errors in these processes, there is evidence that the concepts of classical derivative and weak derivative have been understood by the students. These evidences developed mental mechanisms of reflective abstraction that allowed the construction of the mental structures of action, process, object and scheme present in the genetic decomposition that allowed them to understand the concepts. Moreover, the treatment with the historical context of the derivative and the collaborative work of the students were significant factors to obtain the results of the research.